(untitled) (Web of Teachers: Inderscience Research, 2024)
This article presents the procedure for organizing MICE tourism events in our country, competition in the MICE field, information on the difficulties encountered by enterprises operating in this field in the process of receiving foreign guests, and opinions and comments on foreign experience in the development of this field.